Maintaining Fat-Free Mass and Muscle Mass during obesity therapy with Incretin-Mimetic Drugs - Dariusz Popiela; Karina Urbańska; Łukasz Stojak; Mateusz Grego; Filip Kwiatkowski; Mateusz Baczewski; Katarzyna Grego; Witold Czyż (Quality in Sport)
Obesity is one of the major public health challenges of the 21st century. In recent years, incretin mimetic drugs (IMDs), primarily liraglutide, semaglutide, and tirzepatide, have gained popularity due to their ability to help patients lose 10%-20% of their body weight. However, it has been observed that during treatment with these medications, patients also lose fat-free mass (FFM) and muscle mass (MM). Available scientific knowledge provides limited information regarding preventing FFM and MM loss associated with IMDs treatment. This study aims to analyze current information about strategies that minimize the loss of FFM and MM and muscle function and consider using methods to prevent muscle atrophy in patients treated for obesity with other methods, such as diet, exercise, and bariatric surgery, to form a holistic approach for patients treated with IMDs. This review was conducted by searching scientific publications on PubMed, Google Scholar, and Clinicaltrials.gov databases. The analysis included articles concerning FFM and MM loss in the most common obesity treatment therapies and articles that provided information about the impact of exercise and nutrition combined with IMDs in obesity treatment and proper weight maintenance. The research findings indicate that two primary factors significantly influence the preservation of FFM and muscle mass MM during weight loss therapy: proper nutrition and physical activity. During weight loss interventions, diets should consist of adequate high-quality protein, which contributes to reducing MM loss. Furthermore, physical activity, particularly resistance training, demonstrates a markedly positive effect on the maintenance of MM. All patients undergoing obesity treatment with IMDs must participate in comprehensive programs that offer an appropriate dietary regimen and individually tailored physical exercise plans.